OPTIMALISASI VISUAL BRANDING DESTINASI WISATA KAMPUNG JAMBANGAN SURABYA MELALUI BUKU VISUAL FOTOGRAFI - Wulandari, Sri; Widyasari, Widyasari; Setiawan, Bayu; Iqbal, Muhammad Raihan; Kamal, Musthofa (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2024)
Destination branding is the primary focus of this study, which examines Kampung Wisata Jambangan located in Surabaya, East Java. Kampung Jambangan is a traditional area recognized for its numerous achievements, including the Kalpataru Award (2008) and the Surabaya Tourism Awards (2023). The village possesses significant potential through its flagship programs, such as hydroponics, eco printing, eco enzymes, waste bank management, and river water management. However, both domestic and international tourists remain largely unaware of Kampung Jambangan's tourism potential. This research aims to address the low visibility of Kampung Jambangan as a tourist destination by implementing visual branding through the creation of a photography-based visual book that highlights the unique visual aspects of the village. The research employs a qualitative method with a visual ethnography approach. Visual ethnography is a research method that utilizes images and visual media as primary tools for collecting, analyzing, and presenting ethnographic data. In this context, visuals serve not only as illustrations but also as key elements that enhance the understanding and depiction of social interactions and cultural contexts. Data collection techniques include interviews, observations, and literature reviews. The outcome of this study is a photography-based visual book designed to strengthen the visual identity of Kampung Jambangan, with the intention of increasing its appeal to both domestic and international tourists.